1985
DOI: 10.1093/carcin/6.8.1189
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cembratriene-4,6-diol as antitumor-promoting agent from cigarette smoke condensate

Abstract: Cigarette smoke condensate (CSC) was separated into several fractions and each was tested for an inhibitory effect on the early antigen (EA) of Epstein-Barr virus (EBV) which can be induced by 12-O-tetradecanoylphorbol-13-acetate (TPA) in Raji cells. Two diastereoisomers of 2,7,11-cembratriene-4,6-diol (alpha- and beta-CBT) were isolated from the neutral fractions of CSC and these showed potent inhibitory effects on the induction of EBV-EA by TPA. The doses of alpha- and beta-CBT required for 50% inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 0 publications
0
35
0
Order By: Relevance
“…They were screened for inhibition of the induction of Epstein-Barr virus early antigen in Raji cells by TPA. 1) Sarcophytol A, derived from marine organisms, was screened since it is structurally related to α-CBT and β-CBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were screened for inhibition of the induction of Epstein-Barr virus early antigen in Raji cells by TPA. 1) Sarcophytol A, derived from marine organisms, was screened since it is structurally related to α-CBT and β-CBT.…”
Section: Discussionmentioning
confidence: 99%
“…1) Based on the structural similarity of α-CBT to sarcophytol A, isolated from the soft coral Sarcophyton glaucum, 2) we found that sarcophytol A inhibited tumor promotion on mouse skin by three TPA-type tumor promoters (TPA itself, teleocidin, and aplysiatoxin), and okadaic acid.…”
mentioning
confidence: 95%
“…1), which are the major components in the cuticular wax of Nicotiana tabacum [1], inhibited the promoting ef fect of 12-O-tetradecanoylphorbol-13-acetate (TPA), a potent tumor promotor, on skin tumor formation in mice initiated with 7,12-dimethylbenz[a]anthracene [2]Up to date, TPA has been studied in many systems and has been shown to induce many biological events both in vitro and in vivo. These effects include induc tion of ornithine decarboxylase (ODC) [3,4], induc tion of Epstein-Barr-virus-associated early antigen [5], stimulation of the incorporation of inorganic phos phate into phospholipids [6], activation of membranebound enzymes such as phospholipase A2 [7], and activation of Ca2 +-activated phospholipid-dependent protein kinase (protein kinase C) [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…2 ) cx-and P-CBT also inhibited the induction of ornithine decarboxylase activity by TPA in mouse epiderrnis 2 ); this short-term in vivo assay system is used for detecting tumor promoters 4 )' and anti-tumor promoters. S ) Furthermore, these CBT inhibited the promoting effect of TPA on skin tumor formation initiated with 7,12-dimethylbenz[a]anthracene in mice.…”
mentioning
confidence: 96%
“…S ) Furthermore, these CBT inhibited the promoting effect of TPA on skin tumor formation initiated with 7,12-dimethylbenz[a]anthracene in mice. 2 ) These results prompted us to examine the relationship between the anti-tumor promoting activity and the structure of CBT and its derivatives. In this study, we tested the inhibitory effects of CBT derivatives on the induction of EBV-EA by TPA.…”
mentioning
confidence: 99%